THE EFFECT OF JIGSAW-TYPE COOPERATIVE LEARNING ON MOTIVATION AND ACADEMIC ACHIEVEMENT IN INFORMATICS EDUCATION: A QUASI-EXPERIMENTAL STUDY AT VOCATIONAL HIGH SCHOOL - Fahrur Rozi; Erma Rohmawati (STKIP PGRI TULUNGAGUNG, 2024)
Conventional lecture-based instruction in vocational Informatics education frequently leads to passive engagement and suboptimal learning outcomes among students. Objective: This study investigates the effect of the Jigsaw-type cooperative learning model on students' learning motivation and academic achievement in the Informatics subject at State Vocational High School 2 (SMK Negeri 2) Tulungagung, Indonesia. Methods: A quasi-experimental design with a Non-equivalent Control Group pre-test/post-test structure was employed. The experimental group (Class X-A, n = 30) received Jigsaw-based instruction over four weeks, while the control group (Class X-B, n = 30) continued with conventional lecture-based learning. Learning motivation was assessed using a validated Likert-scale questionnaire (Cronbach's α = 0.87), and academic achievement was measured through pre-test and post-test instruments. Data were analyzed using the Independent Sample T-Test following normality (Kolmogorov-Smirnov) and homogeneity (Levene's) prerequisite tests. Results: The analysis revealed significant differences between groups for both motivation (sig. = 0.001, t = 3.412, Cohen's d = 0.78) and learning outcomes (sig. = 0.000, t = 4.186, Cohen's d = 0.91), with the experimental group demonstrating substantially higher post-test scores (M = 82.4, SD = 6.3 vs. M = 71.6, SD = 7.1). Conclusion: The Jigsaw cooperative learning model significantly enhances both motivation and academic achievement in Informatics education at the vocational level. The peer-teaching mechanism inherent in the Jigsaw structure reduces learning anxiety and promotes active knowledge construction, particularly effective in technical subjects such as Microsoft Excel. These findings provide empirical support for the pedagogical shift from teacher-centered to student-centered instruction in vocational ICT education in Indonesia.